2022
DOI: 10.1002/mp.15442
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐high dose rate electron beams and the FLASH effect: From preclinical evidence to a new radiotherapy paradigm

Abstract: In their seminal paper from 2014, Fauvadon et al. coined the term FLASH irradiation to describe ultra-high-dose rate irradiation with dose rates greater than 40 Gy/s, which results in delivery times of fractions of a second. The experiments presented in that paper were performed with a high-dose-per-pulse 4.5 MeV electron beam, and the results served as the basis for the modern-day field of FLASH radiation therapy (RT). In this article, we review the studies that have been published after those early experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
102
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 80 publications
1
102
0
2
Order By: Relevance
“…First, most solid tumors are known to not be uniformly hypoxic, having both hypoxic and non-hypoxic compartments throughout the tumor [ 22 ]. Under the transient hypoxia hypothesis, this heterogeneity should then introduce a sparing effect also on tumors, which is not supported by the literature [ 9 ]. Second, in vitro studies of normal, non-immortalized cells have shown a sparing effect when irradiated in ambient air conditions (pO2 ≈ 159 mmHg) [ 23 , 24 , 25 , 26 ].…”
Section: Mechanisms Of the Flash Effectmentioning
confidence: 89%
See 2 more Smart Citations
“…First, most solid tumors are known to not be uniformly hypoxic, having both hypoxic and non-hypoxic compartments throughout the tumor [ 22 ]. Under the transient hypoxia hypothesis, this heterogeneity should then introduce a sparing effect also on tumors, which is not supported by the literature [ 9 ]. Second, in vitro studies of normal, non-immortalized cells have shown a sparing effect when irradiated in ambient air conditions (pO2 ≈ 159 mmHg) [ 23 , 24 , 25 , 26 ].…”
Section: Mechanisms Of the Flash Effectmentioning
confidence: 89%
“…Regarding the former, FLASH-RT is a catchy nickname for the novel radiation treatment that uses ultra-high dose rates to deliver radiation therapy (RT). In conventional radiation therapy (CONV-RT) used in most of the world, the dose rate is generally <0.1 Gy/s, whereas the FLASH-RT dose rate is generally defined as a mean dose rate of ≥40 Gy/s [ 8 , 9 ]. A more precise definition is still being debated and will be important to define in order to ensure scientific rigor and to safeguard the clinical translation of FLASH-RT.…”
Section: Flash-rt and The Flash Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…This biological effect, known as the FLASH effect, presents significant benefits to clinical radiotherapy applications. However, clinical application of the FLASH effect is currently hindered by an incomplete understanding of both the precise irradiation parameters necessary to elicit a reproducible FLASH effect as well as the underlying mechanisms [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Confirmed by different groups and on many preclinical models [ 3 , 4 ], the FLASH effect is defined as the combination of a relative absence of normal tissue toxicities compared to isodose of conventional dose rate RT combined with maintained anti-tumor efficacy. It has been observed after exposure of biological tissues to high doses in extremely short treatment times and with specific beam parameters including mean and instantaneous dose rates [ 5 ] mainly, using electrons [ 6 ], but also X-rays [ 7 ] and protons [ 8 ]. As transferring X-ray- and proton-FLASH into the clinics encounters numerous and important technological challenges, FLASH-RT using electrons is the logical first choice to being investigated for the transition from preclinical research to the first clinical applications.…”
Section: Introductionmentioning
confidence: 99%